Paraptosis: a unique cell death mode for targeting cancer - Hanson, Sweata; Dharan, Aiswarya; P. V., Jinsha; Pal, Sanjay; Nair, Bipin G.; Kar, Rekha; Mishra, Nandita (Frontiers in Pharmacology, 2023)
Programmed cell death (PCD) is the universal process that maintains cellular homeostasis and regulates all living systems' development, health and disease. Out of all, apoptosis is one of the major PCDs that was found to play a crucial role in many disease conditions, including cancer. The cancer cells acquire the ability to escape apoptotic cell death, thereby increasing their resistance towards current therapies. This issue has led to the need to search for alternate forms of programmed cell death mechanisms. Paraptosis is an alternative cell death pathway characterized by vacuolation and damage to the endoplasmic reticulum and mitochondria. Many natural compounds and metallic complexes have been reported to induce paraptosis in cancer cell lines. Since the morphological and biochemical features of paraptosis are much different from apoptosis and other alternate PCDs, it is crucial to understand the different modulators governing it. In this review, we have highlighted the factors that trigger paraptosis and the role of specific modulators in mediating this alternative cell death pathway. Recent findings include the role of paraptosis in inducing anti-tumour T-cell immunity and other immunogenic responses against cancer. A significant role played by paraptosis in cancer has also scaled its importance in knowing its mechanism. The study of paraptosis in xenograft mice, zebrafish model, 3D cultures, and novel paraptosis-based prognostic model for low-grade glioma patients have led to the broad aspect and its potential involvement in the field of cancer therapy. The co-occurrence of different modes of cell death with photodynamic therapy and other combinatorial treatments in the tumour microenvironment are also summarized here. Finally, the growth, challenges, and future perspectives of paraptosis research in cancer are discussed in this review. Understanding this unique PCD pathway would help to develop potential therapy and combat chemo-resistance in various cancer.